Integrated S-Library Application with NFC Technology for Information Science - Mohd Kamir, Yusof; Mohd Nordin, Abdul Rahman; Md Yazid, Mohamad Saman (2014)
Information science is related with library and concerned about the collection, record, storage, retrieval, etc. Barcode and Radio Frequency Identification (RFID) is an example of Automatic Identification and Data Capture (AIDC) technology has been implemented in library. RFID technology is introduced to overcome quality of clarity in barcode technology. RFID is successful implemented in information science and the transactions become smooth and effective. This paper presents the innovation technology in information science with development of mobile application. The innovation of technology is knows as Near Field Communication (NFC). This technology is already embedded in selected types of mobile device. S-Library application has been develop and preferred for android platform. The mobile device Samsung Galaxy Note III has been to install Slibrary application. JAVA based was chosen in development of the S-Library application. S-Library application has five major activities. There are scan book, search, borrow, return and transaction. The main function in NFC is to allow users touch the mobile device onto the available NFC tag at the book. The transactions is automatically update in Library Management System (LMS). S-Library application gives more alternative approach to users in information science. S-Library can install into the mobile device and the users can do any library transactions such as book borrows and book returns though the mobile device.